Computational analysis of radiative micropolar fluid flow over a curved stretching sheet with viscous dissipation - Bal Krishn Vaishnav; Sushila Choudhary; Prasun Choudhary; Kavita Jat; K. Loganathan; S. Eswaramoorthi (Discover Applied Sciences)
Abstract This study aims to investigate the mass and heat transmission in a magnetohydrodynamic micropolar fluid over a curved stretching sheet. It focuses on the combined effects of thermal radiation, chemical reaction and porosity via velocity, temperature, concentration and microrotation profiles. Curvilinear coordinates are employed to delineate the fundamental equations of the model. Through suitable transformations, the flow governing partial differential equations are converted into a system of ordinary differential equations accompanied by relevant boundary conditions. These reduced differential equations are resolved numerically with the bvp4c solver in MATLAB package. The significance of the controlling parameters on mass and heat transport characteristics is presented and analyzed graphically. In the $$r$$ r - or $$s$$ s -direction, the fluid’s velocity lowers as the magnetic field strength improves as the Lorentz force inhibits the fluid’s motion. A larger radius of curvature leads to a reduction in thermal profile within the boundary layer. The local heat transfer rate at the surface diminishes as the magnetic parameter raises while it increases with increasing the values of radiation parameter. Findings of this study related to regulated thermal radiation is crucial for various uses, such as polymer processing, spectroscopy, optoelectronic and energy conversion devices.